The possible present - Perone, Ugo (SUNY series in contemporary Italian philosophy, 2011)
Machine generated contents note:ch. OneDramaturgy of Thought --Warning for the Non-Philosopher --Ice Sheet --Time under the Microscope --Finite Time --Present and Presence --ch. TwoPresent as Threshold --Present Is Not Presence but Divide, Condition of Temporality --Features of the Threshold --Spatiality of the Threshold: Outside/Inside --Temporality of the Threshold: Past/Future --After Modernity: The Rediscovery of the Present --Complexity and Consistency of the Present --ch. ThreeEthics of the Present --Education, as Accumulation of Present --Present of the Institution --For cm Ethics of the Present --Beyond Virtues: The Reasons of Tenderness --ch. FourTale without Author --Tale of Philosophy --Tales and Distensio Temporis --Tale without Author --Ontological Proof: Existence That Has Always Already Been There --ch. FiveTale of the I --Tale of the I --I as a Me --Vicissitudes of the I --Coordinates of the I's Journey --ch. SixTale of Finitude --Tale of Finitude --Finite Existence --Infinite Existence --Praise of Lingering --ch. SevenGreat Tale of Time --Tale as Diction of the Present --Beyond as the Already-Been, that is: Naivete in Front of Us --Before the End and After the Beginning: Philosophy --Praise of Philosophy --ch. EightHermeneutics of the Positive --Almost a Conclusion --Positivity of Philosophy --Praise of Dangerous Mediation.